Experimental Implementation and Analysis of Microwave Power Dividers and Directional Couplers - Imad Ali; Nasir Saleem (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2024)
In radio technology, directional couplers and power dividers play a vital role. These devices have well-established theories; however, their performance is not studied under diverse input voltages (and frequencies). This article analyzes the aforementioned devices via extensive laboratory hardware experiments under various input voltages and frequency band settings. The splited power is measured and examined at detectors and ports, while additional parameters, including Insertion Loss and Directivity, are used. The experimental analysis of microwave devices is examined for the power split over a band of frequencies. Our experimental results over a frequency band of 2.0 to 3.0 GHz (with a step size of 0.1 GHz) show that transmitted power at low frequencies is equal and is slightly affected at higher frequencies while the power splitting characteristic over a band of frequencies matches their theories.